The Role of Threats in the Support of System-Justifying Beliefs - Irina S. Prusova; Anna S. Gorokhova (Psychology in Russia: State of Art)
Background. Encounters with threats can lead to a motivation to justify the existing social system, which can be expressed through endorsement of system-justifying beliefs. Objective. The aim of the study was to examine how different types of threats contribute to endorsement of system-justifying beliefs in the economic domain. Design. We tested a theoretical model (N = 577) with internal threats (fear of death), economic threats (threats of poverty and socio-economic inequality), and subjective threat perception (belief in a dangerous and competitive world) as predictors; system-justifying beliefs (economic system justification, opposition to equality, dominance, and antiegalitarianism) served as dependent variables, and sociodemographic characteristics were included as control variables. Results. Structural equation modeling showed adequate fit in the Russian context. Belief in a competitive world positively predicted dominance, antiegalitarianism, and opposition to equality, while belief in a dangerous world negatively predicted economic system justification. Fear of death positively predicted opposition to equality, whereas perceived economic threats (poverty and inequality) negatively predicted antiegalitarianism, and opposition to equality. Conclusion. Dangerous and competitive worldviews, internal and economic threats contribute to the support of system-justifying beliefs in the economic domain.